Effect of different methods of cutting fluid application on turning of a difficult-to-machine steel (SAE EV-8) - De Angelo Sanchez, Luiz Eduardo [UNESP]; Palma, Geraldo L. [UNESP]; Marinescu, Ioan; Modolo, Delson L. [UNESP]; Nalon, Luis J. [UNESP]; Santos, Alex E. [UNESP] (SAGE Publications, 2013)
In this study, different methods of cutting fluid application are used in turning of a difficult-to-machine steel (SAE EV-8). Initially, a semisynthetic cutting fluid was applied using a conventional method (i.e. overhead flood cooling), minimum quantity of cutting fluid, and pulverization. A lubricant of vegetable oil (minimum quantity of lubricant) was also applied using the minimum quantity method. Thereafter, a cutting fluid jet under high pressure (3.0 MPa) was singly applied in the following regions: chip-tool interface, top surface of the chip (between workpiece and chip) and tool-workpiece contact. Moreover, two other methods were used: an interflow between conventional application and chip-tool interface jet (combined method) and, finally, three jets simultaneously applied. In order to carry out these tests, it was necessary to set up a high-pressure system using a piston pump for generating a cutting fluid jet, a venturi for fluid application (minimum quantity of cutting fluid and minimum quantity of lubricant) and a nozzle for cutting fluid pulverization. The output variables analyzed included tool life, surface roughness, cutting tool temperature, cutting force, chip form, chip compression rate and machined specimen microstructure. Among the results, it can be observed that the tool life increases and the cutting force decreases with the application of cutting fluid jet, mainly when it is directed to the chip-tool interface. Excluding the methods involving jet fluid, the conventional method seems to be more efficient than other methods of low pressure, such as minimum quantity of volume and pulverization, when considering just the cutting tool wear. © 2013 IMechE.
Keywords: Cutting fluid jet; cutting force; minimum quantity of fluid; pulverization; tool life; Chip-tool interfaces; Conventional methods; Cutting fluid application; Cutting forces; Tool life; Tool temperatures; Tool-workpiece contact; Comminution; Cutting; Cutting tools; Grinding (machining); Machine tools; Surface roughness; Vegetable oils; Cutting fluids